Quantifying the shape of the maximal expiratory flow–volume curve in mild COPD - Dominelli, Paolo B.; Foster, Glen E.; Guenette, Jordan A.; Haverkamp, Hans C.; Eves, Neil D.; Dominelli, Giulio S.; Henderson, William R.; O’Donnell, Denis E.; Sheel, A. William (Respiratory physiology & neurobiology, 2015)
•The slope-ratio (SR) quantifies the shape of maximal expiratory flow–volume curves.•Compared to matched controls, COPD patients had a greater average SR.•Unlike controls, COPD patients had a SR that increased with lung volume.•The SR could be an additional metric to aid in COPD diagnosis. Maximal expiratory flow–volume (MEFV) curve evaluation using absolute and percent predicted values of flow and volume are used to diagnose respiratory disease, but the shape of the curve is rarely used. Three mathematical methods were used to quantify shape of MEFV curves in subjects with mild COPD (n=19) and matched healthy controls (n=15). Those with mild COPD had a significantly greater slope-ratio (SR) (1.90±0.24 vs. 1.28±0.32) and Beta-angle (160±6.7 vs. 186±15.0) compared to healthy individuals (p<0.05). The flow-ratio method showed no difference between groups. A significant positive SR-volume relationship during expiration was observed in a greater number of mild COPD subjects (94%) compared to controls (20%) (p<0.001). With its increased spatial resolution and the potential to discern etiology behind specific curvature, we suggest using the SR method when available. The change in SR throughout expiration could help identify those who fall within the lower limit of normal lung function and those who may have pathological obstruction.